Screening and Merger Activity - Albert Banal-Estanol; Paul Heidhues; Rainer Nitsche; Jo Seldeslachts (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
In our paper targets, by setting a reserve price, screen acquirers on their (expected) ability to generate merger-speci?c synergies. Both empirical evidence and many common merger models suggest that the di?erence between high- and low-synergy mergers becomes smaller during booms. This implies that the target's opportunity cost for sorting out relatively less ?tting acquirers increases and, hence, targets screen less tightly during booms, which leads to a hike in merger activity. Our screening mechanism not only predicts that merger activity is intense during economic booms and subdued during recessions but is also consistent with other stylized facts about takeovers and generates novel testable predictions.
urn:nbn:de:bvb:19-epub-13282-5
Keywords: 330; Takeovers; Merger Waves; Defense Tactics; Screening; Fusion; Übernahme; Konjunktur; Industrieökonomik; Theorie